Self-care behaviors related to COVID-19 among Iranian elderly with and without a history of infection - Saeed Khayat Kakhki; Shahzad Pashaeypoor; Reza Negarandeh; Leila Sadeghmoghadam (Tehran University of Medical Sciences, 2023)
Background & Aim: Adopting self-care behaviors is considered an important factor in the prevention of COVID-19. Therefore, this study was conducted to investigate Self-Care Behaviors Related to COVID-19 among Iranian elderly with and without a history of infection. Methods & Materials: This descriptive-correlational study was conducted on 324 elderlies in Iran in 2021. Eligible seniors were selected by convenience sampling and placed into two groups:  the elderly with a history of COVID-19, and the elderly without it. The data collection tools included the demographic form and the questionnaire on self-care behaviors during the COVID-19 pandemic. Data analysis was done with SPSS software version 25 using descriptive (frequency and percentage) and inferential statistics (Mann-Whitney u-test and independent t-test). Results: 165 men (50.90%) and 159 women (49.10%) participated in this study. The mean age of the participants was 70.60 ± 8.73. The results showed that there was a statistically significant difference between the self-care behaviors of the elderly with a history of COVID-19 and those without it; the elderly with a history of COVID-19 had more favorable self-care behaviors (p<0.001). Conclusion: A history of COVID-19 results in better self-care behaviors. It can be justified by constructs of the health beliefs model including perceived susceptibility, severity, and treatment. Therefore, it is necessary to improve self-care behaviors by using the experiences of infected elders in health education to influence the above mention constructs.